Biology Learning Based on Socio-Scientific Inquiry: Development of Student Worksheets for Understanding the Concept of Biodiversity - Miftahuddin Miftahuddin; Ummi Nur Afinni Dwi Jayanti (Universitas Labuhanbatu, 2024)
In general, if students do not understand the concept of learning, it affects learning. Therefore, there is a need for teaching materials that convey to students the need to understand concepts when learning. This development research aims to produce student worksheets based on Socio Scientific Inquiry that are valid, practical, effective for students, student sheets, media and material expert validation sheets, as well as practicality sheets. Then the effectiveness sheets are in the form of post-test pretest sheets. Based on the data obtained, the validation of teaching materials had a score of 95.76 %, the results of material validation were 100 %, the teacher response results were 100% and the student response questionnaire results were 95.32 %. The effectiveness assessment resulted in an N-Get of 75.52 % in the high category. Therefore, it can be said that the Socio Scientific Inquiry of worksheet is available, useful, and efficient learning tool that can improve students' conceptual comprehension. However, additional research development can increase the topic of study and include biological learning materials not covered in this worksheet.